Mapping value orientations in Central and Eastern Europe - Halman, Loek.; Voicu, Mălina. (European Values Studies, 2010)
Since the dramatic events in 1989 and 1990, Central and Eastern Europeans have been engaged in a process of democratization and liberalization which are transforming their societies fundamentally. The rapid transformation processes appear to be very differential and the particular patterns are complex to interpret and understand. This volume elaborates on a number of issues that seem particular important for the people in Central and Eastern Europe: the development and working of democracy, the public support for, legitimacy and efficacy of democracy and the free market economy, and of course the stability of the newly established political culture.